The age of unpeace how connectivity causes conflict - Leonard, Mark 1974- (Penguin Books, 2022)
"We thought connecting the world would bring lasting peace. Instead, it is driving us apart. In the three decades since the end of the Cold War, global leaders have been integrating the world's economy, transport and communications, breaking down borders in the hope of making war impossible. In doing so, they have unwittingly created a formidable arsenal of weapons for new kinds of conflict and the motivation to keep fighting. Troublingly, we are now seeing rising conflict at every level, from individuals on social media all the way up to nation-states in entrenched stand-offs. The past decade has seen a new antagonism between the US and China; an inability to co-operate on global issues such as climate change or pandemic response; and a breakdown in the distinction between war and peace, as overseas troops are replaced by sanctions, cyberwar and the threat of large migrant flows. As a leading authority on international relations, Mark Leonard has been inside many of the rooms where our futures, at every level of society, are being decided - from Facebook HQ and facial-recognition labs in China to presidential palaces and remote military installations. In seeking to understand the ways in which globalization has broken its fundamental promise to make our world safer and more prosperous, Leonard explores how we might wrest a more hopeful future from an age of unpeace"--Publisher's description
Keywords: Internationale Politik; Risikofaktor; Politischer Prozess; Entwicklung; Gesellschaft; Internationale Kooperation; Globalisierung; Internationaler Konflikt; Globalization; War; World politics / 1989-; Culture conflict; Armed Conflicts; Mondialisation; Guerre; Politique mondiale / 1989-; Conflit culturel; globalism; World politics; Since 1989; Informational works